Syrian Arab Republic Electricity Sector Strategy Note - World Bank (Washington, DC, 2014)
This electricity sector strategy note was prepared by the World Bank, at the request of the Government of Syria. It identifies options for the Government to improve the financial and technical performance of the electricity sector. The note focuses in particular on the following major sector objectives: a) increasing the efficiency of the electric power sector, including by reducing large technical and commercial losses now standing at 27 percent of demand; b) reducing the growing gap between demand and supply of electricity through capacity expansion, thus enhancing security of electricity supply and reducing power outages; c) increasing security of supply further in an environmentally sustainable manner by developing vigorous energy efficiency and renewable energy programs; d) encouraging regional energy integration through a series of targeted investments in electric power and natural gas; e) attracting private sector investment into generation capacity expansion, including in renewable energy, through independent power producers; and f) making the electricity sector financially viable and coordinating natural gas production plans with electricity generation requirements.